Crassula, insights into an old, arid-adapted group of southern African leaf-succulents - Bruyns, P V; Hanáček, P; Klak, C (Molecular phylogenetics and evolution, 2019)
The Crassulaceae is an important family in the Greater Cape Floristic Region of southern Africa and is the seventh largest family in the arid Succulent Karoo Biome. After the Aizoaceae it is the largest group of leaf-succulents in southern Africa. This is the first investigation of a broad selection (68%) of the ±170 species of Crassula. We used data from three chloroplast and two nuclear gene-regions, which yielded many informative characters and provided good resolution among the species. We show that only five of the 20 sections in Crassula are monophyletic. However, the clades recovered show close correlation with the two subgenera that were once recognized. Crassula contains more than 25 succulent annual species which are not closely related to each other but form early-diverging branches in each of the three major clades. One of these major clades contains far more perennial species than the others and is the greatest diversification within Crassula. This diversification mostly arose within the last 10 million years (my) and spread across much of southern Africa. Members of the smaller two major clades are often soft- and flat-leaved perennials (many with basic chromosome number x = 8, with high levels of polyploidy). Those in the largest diversification (where a basic chromosome number of x = 7 predominates) show other arid-adaptations (more highly succulent leaves with a dense covering of hairs or papillae or a smooth xeromorphic epidermis). Their flowers are also more variable in shape and bee-, moth- and butterfly-pollinated species are known among them. We establish that Crassula arose in the Greater Cape Floristic Region of southern Africa. While much of its diversity has evolved in the last 10 my, Crassula nevertheless contains species that are much older and itself arose ±46 my ago. Since all its species are succulent it is possible that they are part of an early arid-adapted flora that contributed to the Succulent Karoo Biome in the western part of southern Africa. Consequently this Biome may not be assembled only from 'young lineages' as is usually thought to be the case.
Keywords: chloroplasty; Phylogeny; pouštní klima; Adaptation, Physiological; genetické markery; Africa, Southern; Crassulaceae; zvířata; jižní Afrika; časové faktory; Desert Climate; fylogeneze; Genetic Markers; Bayesova věta; fyziologická adaptace; Chloroplasts; Animals; Time Factors; Bayes Theorem